The Effect of Kicking Exercises Using Ankle Weight Modifications on the Results of Soccer Long Distance Kicks in Class VII Students at SMP Negeri 2 Ujan Mas - Deffri Anggara (Sinar Sport Journal, 2021)
The purpose of this study was to improve the long-distance kick results of Class VII students at SMP Negeri 2 Ujan Mas. In this study, the population was male students of Class VII at SMP Negeri 2 Ujan Mas as many as 46 people using random sampling technique by ordinal pairing, namely dividing two groups, 23 experimental groups and 23 control groups. The method in this study used a simple random sampling technique with an ordinal pairing system. The technique used to collect data is a test technique, data analysis technique using t test. The results of data processing and analysis show that the data is normally distributed and homogeneous, then hypothesis testing can be performed using the t-test, so that tcount = 2.881 and ttable = 1.669. Testing the hypothesis is to accept Ha if tcount > ttable and reject Ho if tcount < ttable based on the results of the calculations that have been carried out, it is obtained tcount = 2.881 > ttable = 1.669 where ttable is obtained from interpolation calculations.